Building a Safer School Culture through the Implementation of Pancasila Student Character Values - Setiawati, Setiawati; Eti Hayati; Neng Nurhemah (Cita konsultindo, 2023)
SMAN 6 South Tangerang City is one of twelve public schools located in the South Tangerang city environment and is a school that is preparing itself to become one of the leading schools of choice for the people of South Tangerang City, SMAN 6 South Tangerang City chooses a superior school with the tagline Safer School, namely safe and fun schools and has a goal including Making the school a place to build the nation's character and awareness of environmental culture by increasing intelligence, knowledge, personality, noble character, as well as implementing the six character values of Pancasila students through intra-curricular activities, Extra-curricular / self-development and school culture. SMAN 6 south Tangerang city as an educational institution that has an obligation to prepare a generation with noble character and maintain the preservation of the culture belonging to the Indonesian nation and provide education and maintain norms and life attitudes based on Pancasila. The concept of Safer School is defined as a program to realize safe, clean, healthy, caring, and comfortable conditions, which are able to guarantee the fulfillment of children's rights and protection from violence and, discrimination, and other mistreatment, while the child is in the education unit, as well as supporting children's participation, especially in planning, policy, learning and supervision. Safer School is not building a new school, but conditioning a school to be comfortable for the child, as well as ensuring the school fulfills the rights of the child and protects it, because the school becomes a second home for the child, after his own home. This study aims to; 1) to find out the implementation of the character values of Pancasila students in building a Safer School culture at SMA Negeri 6 South Tangerang City; 2) to find out the supporting and inhibiting factors in building a Safer School culture through the implementation of the character values of Pancasila students of SMA Negeri 6 South Tangerang City. This research uses qualitative methods. Data sources are obtained from observations, interviews, and documentation. Data analysis refers to the inductive analysis of data which includes the collection, reduction, presentation of data, and drawing conclusions or verification. The research output is planned to be published in a national journal